Streptococcus pneumoniae colonization after introduction of 13-valent pneumococcal conjugate vaccine for US adults 65 years of age and older, 2015–2016. Issue 8 (14th February 2019) - ,; Bower, Mary; McNair, Nina; Williams, Sabrina; Presmanes, Emily; Tunali, Amy; Thomas, Stephanie; Hollick, Rosemary; Langdon, Jacqueline; Salar Sepehri, Amir; Sharova, Anna; Milucky, Jennifer; et al.
Abstract: Background: Vaccination of children with 13-valent pneumococcal conjugate vaccine (PCV13) led to declines in vaccine-type pneumococcal nasopharyngeal carriage among adults through indirect effects. In August 2014, PCV13 immunization of all U.S. adults ≥65 years of age was recommended. This study sought to define prevalence and serotype distribution of pneumococcal carriage among adults ≥65 years of age and to describe risk factors for colonization soon after introduction of PCV13 in adults. Methods: A cross-sectional survey of non-institutionalized U.S. adults ≥65 years of age was conducted in four states in 2015–2016. Demographic information, risk factors for disease, PCV13 vaccination history, and nasopharyngeal (NP) and oropharyngeal (OP) swabs were collected. NP and OP swabs were processed separately and pneumococcal isolates were serotyped by Quellung reaction. Antimicrobial susceptibility of pneumococcal isolates was performed. NP swabs also underwent real-time PCR for pneumococcal detection and serotyping. Results: Of 2989 participants, 45.3% (1354/2989) had been vaccinated with PCV13. Fifty-five (1.8%) carried pneumococcus (45 identified by culture and 10 by real-time PCR only) and PCV13 serotypes were found in eight (0.3%) participants. Almost half (22/45) of pneumococcal isolates were not susceptible to at least one of the antibiotics tested. Vaccine-type carriage among vaccinated and unvaccinated individuals was similar (0.2% vs. 0.1%, respectively). Respiratory symptoms were associated with higher odds of pneumococcal colonization (adjusted OR: 2.1; 95% CI = 1.1–3.8). Conclusions: Pneumococcal carriage among non-institutionalized adults ≥65 years of age was very low. Less than 0.5% of both vaccinated and unvaccinated individuals in our study carried vaccine-type serotypes. Over a decade of PCV vaccination of children likely led to indirect effects in adults. However, given the low vaccine-type carriage rates we observed in an already high PCV13 adult coverage setting, it is difficult to attribute our findings to the direct versus indirect effects of PCV13 on adult carriage.